2018
DOI: 10.5194/acp-2018-605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical profiles of sub-3 nm particles over the boreal forest

Abstract: <p><strong>Abstract.</strong> This work presents airborne observations of sub-3 nm particles in the lower troposphere and investigates new particle formation (NPF) within an evolving boundary layer (BL). We studied particle concentrations together with supporting gas and meteorological data inside the planetary BL over a boreal forest site in Hyytiälä, Southern Finland. The analysed data were collected during three flight measure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the other hand, if the 2-4 nm ions are present but they do not grow to form 7-25 nm particles, the time period is classified as an ion burst (IB). Moreover, if 2-4 nm ions are not present, but we observe an increase in the particles, this leads to the assumption that the NPF event did not occur at the measurement location but was carried horizontally or vertically to our site (Leino et al, 2018). The latter has been previously described as a tail event (Buenrostro Mazon et al, 2009) or a TE.…”
Section: Event Classification Decision Treementioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, if the 2-4 nm ions are present but they do not grow to form 7-25 nm particles, the time period is classified as an ion burst (IB). Moreover, if 2-4 nm ions are not present, but we observe an increase in the particles, this leads to the assumption that the NPF event did not occur at the measurement location but was carried horizontally or vertically to our site (Leino et al, 2018). The latter has been previously described as a tail event (Buenrostro Mazon et al, 2009) or a TE.…”
Section: Event Classification Decision Treementioning
confidence: 76%
“…The type TE, or transported events (also known as tail events by Buenrostro Mazon et al, 2009), are events with an undetected beginning as it does not occur at the immediate vicinity of our measurement site. Such events could have been initiated outside our measurement site and transported to Hyytiälä (Leino et al, 2018). The aforementioned hypotheses could explain the observation that TE typically occur at around midday or later in the afternoon, while REs tend to occur concurrent with sunrise.…”
Section: Event Classificationmentioning
confidence: 93%
“…The measurement setups changed slightly over the years. Detailed descriptions of the setups on board can be found in previous studies (Leino et al, 2019;Schobesberger et al, 2013;Väänänen et al, 2016).…”
Section: Airborne Measurementsmentioning
confidence: 99%
“…This might be because in the more polluted environments there are high enough concentrations of precursor vapors from anthropogenic sources that NPF can be initiated in the morning inversion and/or within the bulk of the RL. Interestingly though, observations from Hyytiälä using a small instrumented airplane have frequently found nucleation mode particle layers above the ML at a much higher altitude range of ∼ 1500-2800 m above ground and the explanation for these layers is not clear (Leino et al, 2019;Schobesberger et al, 2013;Väänänen et al, 2016). For example, Väänänen et al (2016) found that for the 2013-2014 airborne measurement campaigns 16/36 (∼ 44 %) profiles showed an elevated sub-25 nm particle layer.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum altitude was about 3800 m above sea level. More details about the set up and measurements can be found in Schobesberger et al (2013), Leino et al (2019), Lampilahti et al (2020).…”
Section: Airborne In Situ Measurementsmentioning
confidence: 99%